Implementation of SAW and TOPSIS in Decision Support System to Decide The Best Midfielder in A Football League - Caesar Gracia; Wahyu Tisno Atmojo (Universitas Pendidikan Nasional, 2022)
Football has been one of the most popular sport in the world. In the world of football, there are often debates on determining who the best player of a position is, this debate would be a controversial topic in Football Awards like Ballon d’Or or FIFPro World XI because often, subjective opinions of human are used during the determining process of the best players. The purpose of this journal is to determine the best midfielder in a foot-ball league using a decision support system. The decision support system method used in this research are Simple Additive Weighting (SAW) to normalize and find the weighted sum of each criteria and Technique Order Preference by Similarity to Ideal Solution (TOPSIS) to determine the best alternative from the set of alternatives.The result of this journal will decide the best alterna-tive from a few midfielders that are chosen using a set criteria.